Use of the Distinct Element Method as a Tool to Detect Stability Problems in Deep Spillway Excavations - Botero-Jaramillo, Eduardo; P. Romo, Miguel; Méndez, Bogart; Marengo, Humberto (Tecnología y ciencias del agua, 2014)
This paper describes a study to determine the stability of rock excavations in the La Yesca spillway channel using numerical analysis. The results of the analysis led to implementing important changes in the original conception of the spillway (reorientation, channel geometry and length) in order to ensure rock slope stability under static and seismic conditions. This paper describes the 3D numerical modeling of a 280 m high slope (corresponding to the original project) cut in a rock mass having complex geological formations. The modeling was carried out to evaluate both the static and dynamic stability of the projected rock slope. The construction site presented complex geological features such as faults and dikes as well as several geological formations resulting from varying qualities and fracture conditions. Available field data made it possible to incorporate the most important geological and topographical features. The spillway excavation was simulated using four stages. The effect of blast-induced damage and stress relaxation on the rock mass was also taken into account. After the simulation of the excavation process was completed, the seismic motion design for the La Yesca dam was input. These dynamic analysis simulated the three-dimensional behavior of the spillway which enabled identifying possible block instabilities, thereby determining whether to stabilize them or modify the original spillway layout.